The Viral Efficacy of three Disinfectants on Hepatitis B virus - Arami Sakineh; Aghasadeghi Mohamadreza; Tabatabaie Masome Hasani; Darvishpour Hojat; Sheikhzadeh Sedigheh (Tehran University of Medical Sciences, 2015)
Background and Aims: Hepatitis B is an important infection route in dentistry requiring different disinfectants to prevent its transmission. The aim of this study was to compare the effects of chemical disinfectants (FD366, ISORAPID and 5% sodium hypochlorite 2/100) to remove Hepatitis B infections from the dental surfaces.   Materials and Methods: In this experimental laboratory trial, serum of 10 HBV patients was poured into microtubes, FD366, ISORAPID and hypochlorite disinfectants were added to them. PCR experiments with viral diagnostic kits were used to diagnose the virus genome. Real time PCR was used to evaluate after incubation with the disinfectants. The reductions occurred in the viral load of Hepatitis B were statistically analyzed using Kruskal-wallis and Mann-Whitney U tests .   Results: No significant antiviral efficacy was noted following the application of FD366 and ISORAPID disinfectants (P=0/07). However, hypochlorite showed the most efficacy to disinfect Hepatitis B and a significant difference was found among them (P<0.0001).   Conclusion: Under the study limitations, FD366 and ISORAPID disinfectants did not show adequate efficacy to remove Hepatitis B virus. Hypochlorite was the most effective disinfectant.